The Impact of Organizational Culture and Human Resource Quality on Employee Job Satisfaction in Social Services - Hardiansyah; Nur Amalia (Journal of Social Science and Business Studies, 2024)
This research aims to analyze the positive influence of organizational culture and the quality of human resources on employee performance through job satisfaction. We involved 100 employee respondents in the research and conducted the analysis using the descriptive model and multiple linear regression analysis with the SPSS 25 program. The results of the research show that organizational culture has a positive and significant influence on performance, as does the quality of human resources, which also has a positive and significant influence on employee performance. Apart from that, simultaneously, organizational culture and the quality of human resources also have a positive and significant effect on performance. Another finding is that organizational culture has a positive and significant influence on job satisfaction, as does the quality of human resources, which has a positive and significant influence on employee job satisfaction. Research has proven that job satisfaction significantly and positively affects employee performance. Finally, simultaneously, organizational culture and the quality of human resources have a positive influence on employee performance through job satisfaction. Thus, this research contributes to understanding the complex interactions between organizational culture, quality of human resources, job satisfaction, and employee performance so that it can become a basis for improving and developing management strategies in the organizational environment.